Implementasi Virtual Reality Counseling Berbasis Metaverse untuk Meningkatkan Keterampilan Konseling Guru Bimbingan Konseling Kota Malang - Imam Ariffudin; Ajeng Intan Nur Rahmawati; Akhmad Zaini (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
This community service program aims at enhancing the counseling skills of vocational school guidance and counseling teachers (MGBK) in Malang through the implementation of Virtual Reality (VR) technology based on the metaverse. Initial survey results indicated that most BK teachers faced difficulties in utilizing digital technology, especially VR, and continued to manage counseling services using conventional methods. These challenges affected the effectiveness of service documentation and the comfort of the counseling environment. The program was carried out in four main stages: socialization, training, mentoring, and evaluation. This approach allowed counseling sessions to be conducted online in a flexible way. BK teachers were trained to use konse-link.com as a platform for managing counseling services, including appointment scheduling, documentation, and conducting sessions within a virtual environment. Evaluation results showed significant improvement on teachers’ understanding and skills in using VR and LMS platforms, along with an increase in the frequency of services provided. Student responses were also positive; they reported feeling more comfortable, open, and supported in expressing their concerns through virtual counseling approaches. This program is expected to serve as a sustainable solution for improving the quality of guidance and counseling services in vocational schools, in line with technological developments in education.